A Concept of Virtual-Flux Direct Power Control of Three-Phase AC-DC Converter - Nor Azizah Mohd Yusoff; Azziddin M. Razali; Kasrul Abdul Karim; Tole Sutikno; Auzani Jidin (Institute of Advanced Engineering and Science, 2017)
This paper presents a proposed technique of virtual-flux direct power control (VF-DPC) as the improvement in control method from the basic of conventional direct power control (DPC) for front-end three-phase pulse width modulated (PWM) in ac-dc converter. Three sensors in order to measure the three phase input voltage have been eliminated in the proposed method of virtual flux (VF) regarding from the estimation technique. Theoritical principles of VF-DPC are discussed in this paper. The steady-state performance of VF-DPC and conventional DPC are evaluated and presented in this work to estinguish for the excellent performance. It is shown that the VF-DPC exhibits the several advantages, particularly in providing low total harmonic distortion with almost sinusoudal of input current and unity power factor (pf) operation under balanced three phase voltage supply. The simulation results from both methods through Matlab simulation have demonstrated the outstanding performance of the new proposed control technique from VF-DPC.